Reshuffling Responsibilities in Old Age: The United States in a Comparative Perspective - Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1997)
It is increasingly clear that the United States has adopted a strategic goal to shift federally-funded entitlement programs from a defined benefit to a defined cost basis. A cross-national comparison, this paper discusses the 1996 Welfare Reform Act and its probable effect on other federal entitlements, such as Medicaid, Medicare, and Social Security. Who will be at-risk as economic and financial responsibilities in old age are reshuffled?
Keywords: 330; Sozialreform; Altersvorsorge; USA